2009
DOI: 10.48550/arxiv.0912.2937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Applications of the Similarity Renormalization Group to the Nuclear Interaction

E. D. Jurgenson

Abstract: The Similarity Renormalization Group (SRG) is investigated as a powerful yet practical method to modify nuclear potentials so as to reduce computational requirements for calculations of observables. The SRG proves to be versatile and robust in its treatment of these interactions and opens the door to a deeper understanding of the renormalization process.Chiral Effective Field Theory (χEFT) provides a consistent and rigorous parametrization of the inter-nucleon interaction. While already softer than other avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
(202 reference statements)
1
3
0
Order By: Relevance
“…[52], as an attempt to determine a priory the final ordering of the spectrum induced by the SRG evolution in the infrared limit. As we will see, the perturbative analysis is well-succeeded in predicting the ordering of the spectrum only in the case of the Wilson generator, although the results for both generators are consistent with the analytical proof of diagonalization of the SRG evolved hamiltonian presented in Refs [7,40].…”
Section: Stability Analysis Of the Infrared Fixed Pointssupporting
confidence: 81%
See 1 more Smart Citation
“…[52], as an attempt to determine a priory the final ordering of the spectrum induced by the SRG evolution in the infrared limit. As we will see, the perturbative analysis is well-succeeded in predicting the ordering of the spectrum only in the case of the Wilson generator, although the results for both generators are consistent with the analytical proof of diagonalization of the SRG evolved hamiltonian presented in Refs [7,40].…”
Section: Stability Analysis Of the Infrared Fixed Pointssupporting
confidence: 81%
“…For a translational invariant system, i.e. V s ≡ V rel s , we can separate the CM and consider only the SRG evolution of the hamiltonian for the relative motion, H rel s = T rel + V rel s , since the CM kinetic energy T cm does not contribute [40]. For simplicity, in what follows we will drop the superscript "rel".…”
Section: Srg Flow Equations In Operator Formmentioning
confidence: 99%
“…Note that all this information is not lost but merely reorganized into NNN terms, and when we keep those terms we regain the unitary result. This analysis is supported by studies in one-dimensional models that showed purely attractive initial potentials to have monotonically decreasing binding energy [13,21].…”
Section: Evolution Of Many-body Forcesmentioning
confidence: 63%
“…These maxima, in the momentum and coordinate space representations, will be correlated with the high and low-momentum cutoffs respectively. These cutoffs have the large N max behavior: [21]…”
Section: Introductionmentioning
confidence: 99%